PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA PADA PT. WIKA BETON SEMARANG - Dara Chatlea Satiti; Margaretha Suryaningsih; Tri Yuniningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
This research is motivated by problems that occurred in the PT. Wika Beton Semarang, such as the low level of productivity. The purpose of this study to analyze influence of motivation and discipline to productivity. To answer the problem and purpose of this study, the author used the theory of productivity using quantitative research methods. In collecting the data, the writer uses tehnique through questionnaire. The informants were the employee of PT. Wika Beton Semarang. The results showed that motivation dan discipline partially and simultaneously positively influenced productivity.